Care of the self and the preparation for free musical improvisation (Orfeu, 2017)
The present article aims to contributeto reflections regarding different processes of preparation for free musical improvisation, with aid of the idea of “care of theself”, as presented by Michel Foucault inthe Hermeneutics of the Subject. The philosopher conducts a study of this conceptand associated practices, among classicGreek philosophers and follows it to thetime of Descartes when it is dissociatedfrom “know thyself”. By way of revision ofFoucault’s work, we shall attempt to describe concepts which may aid us in lookingat practices of preparation for free musicalimprovisation. As reference for studies inthe field of learning musical improvisation,we shall present ideas from researcheswhich bring together music and cognitivesciences. Lastly we shall offer our reflection based on the practices studied herein, and we shall search for tools for thecomprehension of the preparation for freemusical improvisation, which contemplatemore than the motor rehearsal of the actions of the performance.
Keywords: free musical improvisation; preparation; care of the self